Perubahan Perilaku Kesiapsiagaan Bencana Gempa Bumi melalui Penggunaan Disaster Smart Book Health Berbasis Komik pada Siswa Sekolah Dasar - Aditya, Nauval Najib; Sidiq, Rapitos; Widdefrita, Widdefrita; Novelasari, Novelasari; Hayati, Neni Fitra (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2023)
Background. The city of Padang is a potential earthquake area because it is located on the world's tectonic plates. Disaster preparedness efforts must be increased to minimize injuries and fatalities. Aim. This research aims to determine changes in earthquake disaster preparedness behavior through the use of comic-based disaster smartbook health among elementary school students Method. This type of research is a mixed method with a qualitative and quantitative approach. The population used was students at SD Negeri 19 Air Tawar Barat, samples were taken using a non-random sampling method with a purposive sampling technique. Qualitative research using graphic design expert informants, BPBD, and health workers. Data collection uses questionnaires and interview guides. Data processing was carried out using SPSS univariately and bivariate with the Kolmogorov-Smirnov test Result. Comics are made with attractive designs and varied colors adapted from the interview results. The average knowledge obtained before and after the intervention was 5.23 and 8.69, while the average attitude before and after the intervention was 35.21 and 44.17. The research results show that there is a difference in average knowledge (p-value=0.0001) and attitude (p-value=0.0001).